Early Appearance of TNF-α and Other Cytokines in Bronchus Associated Lymphoid Tissues (BALT) from Growing Wistar Rats. What is the Role of TNF-α? - Dreanina Delettieres; Cecilia A. Frecha; Maria E. Roux (Clinical and Developmental Immunology)
Several different cytokines trigger the development of determined cell subsets in BALT of growing Wistar rats. Early appearance (4 days post partum) of γδT cells in BALT has been shown, as well as its role in up-regulating TNF-α production. In the present report, we studied in the BALT: (1) the profile of the cytokines, TNF-α, INF-γ and IL-10 and (2) in TCR γδ+ cells, the existence of a colocalization with TNF-α as well as with INF-γ. All the cytokines studied were observed at an early stage of BALT development by immunohistochemistry and in bronchoalveolar cells (BAL cells) by flow cytometry and western blot. (1) The principal cytokine found at 4 days of age in BALT cells was TNF-α that increases along BALT development. The same behavior was found for cells containing IL-10 and INF-γ. (2) TCR γδ+ cells colocalize mainly with TNF-α as it has been shown by immunohistochemistry in BALT and by flow cytometry when we studied BAL.